Selectivity of Gill Nets for Catla catla (Ham) Cirrhinus mrigala (Day) and Labeo rohita (Ham) in Gandhisagar Reservoir - K.N., Kartha; K.S., Rao (Fishery Technology, 2025)
The results of the selectivity studies on gill nets conducted in Gandhisagar reservoir for exploitation of catla, mrigal and rohu are discussed in this paper. The optimum mesh bar values suitable for the judicious exploitation of commercial size groups of catla, rnrigal and rohu are 148 mm, 89 mm and 60 mm respectively. Out of the three types of gill nets fabricated with nylon twines 210/l/3, 210/2/3 and 210/3/3 to study the effect of twine size, 61.48% catla is caught in 210/2/3 of 0.628 mm dia, and 56.25% and 61.18% mrigal and rohu respectively are caught in gill net with nylon twine 210/l/3 of 0.396 mm dia.